2006
DOI: 10.2113/geoarabia110275
|View full text |Cite
|
Sign up to set email alerts
|

Upper Dalan Member and Kangan Formation between the Zagros Mountains and offshore Fars, Iran: depositional system, biostratigraphy and stratigraphic architecture

Abstract: To better constrain the spatial and stratigraphic distribution of the depositional facies, a synthesis of outcrop and subsurface data for the depositional system of the Upper Dalan Member and Kangan Formation in the Zagros to the offshore Fars area was carried out. The areas that were studied in detail are the Kuh-e Surmeh and Kuh-e Dena sections of the Zagros Mountains, Iran, and their equivalent in the offshore Fars subsurface. The observations and interpretations based on these sections were then integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(64 citation statements)
references
References 37 publications
7
57
0
Order By: Relevance
“…Previous studies (Adolmaleki et al, 2016;Enayati-Bidgoli & Rahimpour-Bonab, 2016;Insalaco et al, 2006;Nazemi et al, 2018;Nazemi et al, 2019;Tavakoli, 2017;Tavakoli & Jamalian, 2019) showed that reservoir zones of the studied formations are different in terms of reservoir quality and sedimentary, diagenetic and routine logs characteristics. Therefore, the variations in DSI logs and their relationship with the type of porosity in each electrofacies have been evaluated in each zone separately.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous studies (Adolmaleki et al, 2016;Enayati-Bidgoli & Rahimpour-Bonab, 2016;Insalaco et al, 2006;Nazemi et al, 2018;Nazemi et al, 2019;Tavakoli, 2017;Tavakoli & Jamalian, 2019) showed that reservoir zones of the studied formations are different in terms of reservoir quality and sedimentary, diagenetic and routine logs characteristics. Therefore, the variations in DSI logs and their relationship with the type of porosity in each electrofacies have been evaluated in each zone separately.…”
Section: Resultsmentioning
confidence: 82%
“…From the Permian to the Triassic, the reactivation of normal faults and the expansion of grabens have been associated with the opening of Neo‐Tethys. At this time in the Zagros and the Qatar Arc–South Fars, the carbonate sediments were deposited on the marginal platform of Pangea (Alavi, 2004; Insalaco et al., 2006).…”
Section: Geological Setting and Stratigraphymentioning
confidence: 99%
“…Dalan Formation is important in connection with exploration and development projects and has been studied by many researchers in the form of oil or university projects. Insalaco et al (2006) have studied the upper part of Dalan Formation and Kangan Formation between Zagros and Fars Mountains and studied these formations in terms of stratigraphy and sedimentation system. Also, Esra li et al (2009) in their article entitled "The effect of diagenesis and leakage environment on the reservoir quality of carbonates in the South Pars gas eld.…”
Section: Introductionmentioning
confidence: 99%
“…These frameworks have provided important regional constraints for tying locally interpreted transgressiveregressive (T-R) sequences (e.g. Strohmenger et al, 2002;Osterloff et al, 2004;Vaslet et al, 2005;Alsharhan, 2006;Insalaco et al, 2006;Al-Husseini, 2008;Maurer et al, 2009;Koehrer et al, 2010) and biostratigraphic zones (e.g. Stephenson et al, 2003;Stephenson, 2006;Angiolini et al, 2004;Vachard et al, 2005;Crasquin-Soleau et al, 2006;Chirat et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Two recent papers have advanced the understanding of the Khuff and equivalent formations much further by documenting the architecture of their higher-order cyclo-stratigraphy. The first study spans the Upper Permian and Lower Triassic in the Fars-Zagros subsurface and outcrops in Iran (Insalaco et al, 2006; Figure 1a). The second covers the Middle Permian to Lower Triassic in the Saiq Plateau of Al Jabal al-Akhdar in Oman (Koehrer et al, 2010;Figure 1b).…”
Section: Introductionmentioning
confidence: 99%